2017
DOI: 10.1017/s0016756817000589
|View full text |Cite
|
Sign up to set email alerts
|

Testing the early Late Ordovician cool-water hypothesis with oxygen isotopes from conodont apatite

Abstract: Latest Sandbian to early Katian sequences across Laurentia's epicontinental sea exhibit a transition from lithologies characterized as 'warm-water' carbonates to those characterized as 'coolwater'carbonates. This shift occurs across the regionally recognized M4/M5 sequence stratigraphic boundary and has been attributed to climatic cooling and glaciation, basin reorganization and upwelling of open ocean water, and/or increased water turbidity and terrigenous input associated with the Taconic tectophase. Documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Similarly, based on the oxygen isotopic composition of sandstone cements, Hyodo, Kozdon, Pollington, and Valley () demonstrated that quartz cements of Ordovician sandstones that underlie the studied limestones formed in a near‐surface environment at low temperatures (~40°C), lending support to the interpretation that the Ordovician rocks never experienced burial depths greater than 500 m (Figure b; Luczaj, ). Furthermore, the conodont alteration index of conodonts extracted from this outcrop is between 1 and 1.5 and supports these temperature estimates (Quinton et al., ), indicating that no alteration of Ce or Eu anomalies occurred due to elevated temperatures.…”
Section: Interpretation and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, based on the oxygen isotopic composition of sandstone cements, Hyodo, Kozdon, Pollington, and Valley () demonstrated that quartz cements of Ordovician sandstones that underlie the studied limestones formed in a near‐surface environment at low temperatures (~40°C), lending support to the interpretation that the Ordovician rocks never experienced burial depths greater than 500 m (Figure b; Luczaj, ). Furthermore, the conodont alteration index of conodonts extracted from this outcrop is between 1 and 1.5 and supports these temperature estimates (Quinton et al., ), indicating that no alteration of Ce or Eu anomalies occurred due to elevated temperatures.…”
Section: Interpretation and Discussionsupporting
confidence: 82%
“…(b) Generalized geohistory plot illustrating the burial history of sediments in eastern Wisconsin since the Ordovician (redrawn from Luczaj, 2006). Several geochemical proxies (e.g., organic maturity, oxygen isotopic composition of sandstone cements, oxygen isotopic composition of conodont apatite) and stratigraphic reconstructions suggest that Ordovician rocks in this area were never buried deeper than 1 km and only experience temperatures lower than 40-60°C (Hyodo et al, 2014;Luczaj, 2006;Quinton et al, 2017) environments ranging from inner ramp to outer ramp depositional settings (Choi & Simo, 1998;Choi, Simo, & Saylor, 1999;Witzke & Ludvigson, 2005).…”
Section: Regional Stratigraphymentioning
confidence: 99%
“…The Sebree Trough stretched for hundreds of kilometers and funneled cool nutrient-rich waters into the craton from the Iapetus Ocean to the south, resulting in deposition of black shales (Kolata et al, 2001). The influx of oceanic water in addition to the deepening of cratonic basins from the Taconic tectophase may have initiated epicontinental estuarine-like circulation patterns in the midcontinent of Laurentia, generating a density-stratified water column that contained cool, oxygen-poor, phosphate-rich oceanic waters that continued until at least the earliest Katian (Wilde, 1991;Kolata et al, 2001;Quinton et al, 2017). Consequently, carbonate platform deposition ceased and a mixed carbonate-clastic facies prevailed within temperate waters across most of east-central Laurentia (Keith, 1989;Ettensohn, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, machine-learning techniques (hereinafter ML) have been applied to volcanology [17,18]. Here, we test whether ML techniques can be applied to these deposits to enhance our ability to identify and correlate these eruptive events that could be used to track environmental and tectonic changes through time and space in order to test tectonostratigraphic hypotheses [5,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%